Translating Research into Policy : New Guidelines for Communicating Rights to Non-Native Speakers - Eades, Diane; Pavlenko, Aneta (Language and Law / Linguagem e Direito, 2017)
The purpose of this article is to introduce the Guidelines for communicating rights to non-native speakers of English in Australia, England and Wales, and the USA. The guidelines were authored by the international Communication of Rights group (CoRG) that brought together 21 linguists, psychologists, lawyers, lawyer-linguists and interpreters. The intention was to “translate” research on the communication of rights to non-native speakers in police interviews for practitioners and policy makers. Drawing on linguistic and psychological research, as well as our collective experience of working with specic cases, CoRG produced a 2000-word guidelines document with seven recommendations, an explanation accessible for police ocers, lawyers, judges and justice administrators, and a bibliography of relevant research. The article explains why this project was restricted to three common law countries, and encourages others to consider using the document, following this article, as a starting point for a similar development in their own country or jurisdiction.